PENGARUH KOMPENSASI DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA PT ASURANSI ASEI INDONESIA - Sihabudin, Ahmad; Setyawasih, Rianti (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The purpose of this study is to determine the effect of compensation and job satisfaction on turnover intention at PT Asuransi Asei Indonesia. The saturated sample used was 90 employees. Data were collected by conducting observations, interviews and dissemination of questionnaires. The data were analyzed using double linear regression with SPSS. The results showed that compensation had a negative and significant effect on turnover intention of -0.360 (?1) as evidenced by a t-count value of -3.196 and a sig value of 0.000. There was also a negative and significant influence of job satisfaction on turnover intention of -0.909 (?2) as evidenced by a t-count value of -8.394 and a sig value of 0.000). The built model is a fit as evidenced by an F-count value of 120,811 and a sig value of 0.000; in this case, compensation and job satisfaction were able to explain the variation in turnover intention by 72.9 percent